2007
DOI: 10.1002/cncr.23044
|View full text |Cite
|
Sign up to set email alerts
|

Annual report to the nation on the status of cancer, 1975–2004, featuring cancer in American Indians and Alaska Natives

Abstract: (1975 through 2004) and fixed-interval (1995 through 2004) incidence and mortality trends were evaluated by annual percent change using regression analyses (2-sided P < .05). Cancer screening, risk factors, socioeconomic characteristics, incidence data, and stage were compiled for non-Hispanic whites (NHW) and AI/AN across 6 regions of the U.S.We thank Andrew Lake, Rick Firth, Danielle Melbert, and Martin Krapcho of Information Management Services, Inc. for assisting in statistical analyses.We also thank Tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
339
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(354 citation statements)
references
References 127 publications
(141 reference statements)
11
339
3
1
Order By: Relevance
“…Colorectal cancer (CRC) is the second most common cause of cancer-related death worldwide (1). Approximately 50% of patients diagnosed with CRC die as a result of complications from distant metastases, which occur mainly in the liver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer (CRC) is the second most common cause of cancer-related death worldwide (1). Approximately 50% of patients diagnosed with CRC die as a result of complications from distant metastases, which occur mainly in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNAs in the development of metastasis has been demonstrated in several cancer types, including breast cancer, hepatocellular carcinomas, head and neck cancer and brain tumors (17). Most studies involving CRC have analyzed the association between miRNAs and microRNA-320a inhibits tumor invasion by targeting neuropilin 1 and is associated with liver metastasis in colorectal cancer metastasis using both in vitro and mouse models. Most tissuebased experiments derived from CRC patients are only able to identify differential miRNAs using primary tumor tissues versus normal tissue (15).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in mammography use and declines in the use of CHRT have both been postulated as a cause for the decrease in overall breast cancer incidence in 2002 (22,(24)(25)(26)(36)(37)(38). However, unlike ductal carcinoma, lobular breast cancer is not detected primarily through mammography.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent trends in CRC incidence and mortality reveal declining rates, which have been attributed to reduced exposure to risk factors, screening's effect on early detection and prevention through polypectomy, and improved treatment. 3 However, in the near term, even greater incidence and mortality reductions could be achieved if a greater proportion of adults received regular screening. Although prospective randomized trials and observational studies have demonstrated mortality reductions associated with early detection of invasive disease, as well as removal of adenomatous polyps, 4-7 a majority of US adults are not receiving regular ageand risk-appropriate screening or have never been screened at all.…”
Section: Introductionmentioning
confidence: 99%